2021
DOI: 10.1158/1078-0432.ccr-21-1295
|View full text |Cite
|
Sign up to set email alerts
|

Results from a First-in-Human Phase I Study of Siremadlin (HDM201) in Patients with Advanced Wild-Type TP53 Solid Tumors and Acute Leukemia

Abstract: Utrecht as recipient); expert testimony form Bristol-Myers Squibb (with FdV as recipient); travel, accommodations from Roche/Genentech (with FdV as recipient).NS reports consultation or acting in an advisory role for AIMM Therapeutics,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Recently published clinical data on siremadlin [ 28 , 33 ] and trametinib [ 29 , 34 ] combined with the findings of this study may support the extrapolation of animal PBPK/PD data into a clinical situation. Nonetheless, due to the limited amount of in vivo drug combination data available from this study, such extrapolation may only predict the initial efficacy in patients.…”
Section: Discussionsupporting
confidence: 77%
“…Recently published clinical data on siremadlin [ 28 , 33 ] and trametinib [ 29 , 34 ] combined with the findings of this study may support the extrapolation of animal PBPK/PD data into a clinical situation. Nonetheless, due to the limited amount of in vivo drug combination data available from this study, such extrapolation may only predict the initial efficacy in patients.…”
Section: Discussionsupporting
confidence: 77%
“…The imidazopyrrolidinone siremadlin is an advanced molecule that has been tested in patients with solid tumors and hematological malignancies harboring no p53 mutations. In a phase I clinical study involving patients with AML, siremadlin has demonstrated promising results ( 28 ). Moreover, siremadlin is being investigated alone or in combination with other drugs in five different clinical trials that are still recruiting patients ( 29 – 34 ).…”
Section: Mdm2 Inhibitorsmentioning
confidence: 99%
“…HDM201 was recently investigated in a phase I, multicenter, open-label trial ( 170 ). In total, 115 patients with treatment-refractory locally advanced or metastatic solid tumors and 93 patients with relapsed or refractory hematologic malignancies were included.…”
Section: Clinical Trial Results For Mdm2 Pathway Inhibitors In Liposa...mentioning
confidence: 99%